Race-ing Time: Clinical Temporalities and Inequality in Public Prenatal Care. Issue 8 (17th November 2019) - Andaya, Elise
ABSTRACT: Analysis of clinical temporalities, or the social organization of time in the clinic, offers insights into how racism coheres in pregnant bodies and institutions, with implications for health care experiences for patients and providers. Based on research at a public prenatal clinic, I argue that long patient wait-times and pressure on providers to speed up are temporal instantiations of the same racist structures that shape public health care in the US. Through these temporal experiences, racialized patient populations and staff who work in racialized systems of public health care encounter the lesser value assigned to their time, bodies, and labor.